Comparison of Multicultural Education in SMP Maria Immaculata Y ogyakarta and SMP 5 Yogyakarta - Taat Wulandari (JOURNAL OF EDUCATION, 2013)
This study aims to describe the ideas of multicultural education from principals, teachers, students, and students' parents. Their ideas and under standings are explored to obtain a description of practices by principals, teachers, students, and students' parents to implement multicultural education in the school life. This study employed the qualitative method. It used the naturalistic inquiry. The  research  subjects  comprised principals,  teachers,  students,  and students' parents in SMP Maria Immaculata Yogyakarta and SMP 5 Yogyakarta. They were selected by means of the purposive  and snowball sampling techniques. The data were collected by means of three techniques, namely observation, interview, and documentation techniques. The research instrument was the researcher herself. The data trustworthiness was enhanced through the triangulation technique, including source  and  data  triangulations.  The  data  were  analyzed  using  the qualitative data analysis by Miles Huberman, consisting of data reduction, data display, and conclusion drawing. After  the investigation of the life in the two schools, the following  conclusions are drawn. 1) Principals,  teachers, students, and   students'   parents    have   awareness   and   understanding   of   individual differences. 2) The conceptualization of the awareness is manifested in the values to   develop,   namely   no   discrimination,   understanding   of   other   people's perceptions, avoidance of stereotypes, attempts for  equality, realization of justice, mutual acceptance, mutual respect, mutual tolerance, empathy, communication, affection, family atmosphere, brotherhood, and tolerance.